Tantangan Hukum Perikatan dalam Kontrak Bisnis Modern: Studi Kasus Pinjaman Online dan Perjanjian Kerjasama - Anita Nurbayiti; Rinda Robyatul Gayatrie; Sefti Trisma Dewi (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
The development of digital technology has significantly transformed modern business practices, particularly in contract execution and legal obligations. One notable innovation is the rise of online lending services powered by financial technology (fintech), which enable rapid loan transactions without face-to-face interactions. While these services increase financial access, they also present serious legal challenges—most notably, anti-competitive behavior. Recently, the Indonesian Competition Commission (KPPU) identified indications of a loan interest rate cartel involving 97 fintech lending platforms affiliated with the Indonesian Joint Funding Fintech Association (AFPI). These entities allegedly agreed to set uniform interest rate caps, not based on market dynamics but through internal consensus, thereby restricting competition and harming consumers. This article examines the impact of such interest rate cartel practices on consumer rights and fair competition in the online lending sector, as well as the legal role of supervisory institutions such as KPPU in addressing these issues. Using a normative juridical method and legal-conceptual approach, the study analyzes relevant legislation, including Law No. 5 of 1999 on Prohibition of Monopolistic Practices and Unfair Business Competition, alongside regulatory measures by the Financial Services Authority (OJK). The study highlights the need for stricter enforcement, adaptive regulation, and institutional synergy to ensure legal certainty and consumer protection in modern contract law, especially in the digital business ecosystem.